Estudo da interação pósitron-matéria em sólidos supramoleculares orgânicos e sistemas aromáticos substituídos - Fernando Castro de Oliveira (2011)
This work reports the preparation, characterization and investigation of intermolecular interactions in [TPPO(1-X)×TFNMX] and TPPO(1-X)×ACTLX] supramolecular complexes and especially the use of EVMP in the investigation of the effect of the formation and/or the structural properties of these complexes on positron-matter interaction sensitivity at a temperature of 294 K and 80 K. Additionally, we conducted an investigation of the electronic effect and the substitution pattern (ortho-, meta- and para-, with -OH, -NH2, - CN and -NO2 groups) in the formation of positronium (Ps) in molecular organic crystals derived from benzene and naphthalene at a temperature of 294 K. The supramolecular systems were characterized by CHN, HPLC, thermal analysis (TGA, DTA andDSC), FTIR-ATR, XRD and EVMP. The results obtained by elemental analysis for [TPPO(1-X)×TFNMX] exhibited good agreement withthose calculated, and the composition of the system were determined by HPLC. The values of melting temperature and enthalpy of fusion for the complex [TPPO0,5×TFNM0,5] are significantly higher than thoseobtained for the isolated precursors, TPPO and TFNM. These results suggest that the interactions in the supramolecular complex [TPPO0,5×TFNM0,5] are stronger than those in the isolated precursors. The stablishment of hydrogen bonding (C6H5)3P=O× × ×H-OC(C6H5)3 was confirmed by FTIR-ATR through the displacement of the phosphoryl (P=O) and hydroxyl (O-H) bands to lower energy region. The X-raycrystallography results obtained from the literature show the shortening of the hydrogen bond in the complex [TPPO0,5×TFNM0,5] in relation to TFNM isolated as well as the existence of an "sixfold phenyl embrace"interaction among the phenyl groups. XRD confirmed the existence of two phases. The results of the o-Ps annihilation parameters as furnished by EVMP at 294 K for TPPO and TFNM are quite similar when the measurements uncertainties are considered. However, the same parameters for the complex [TPPO(1-X)×TFNMX] are significantly affected. The low value of the parameter on the probability of positroniumformation in the complex [TPPO0,5×TFNM0,5] when compared to their isolated precursors was associated with strong interactions formed. The parameter on the lifetime of the o-Ps, which can be associated with themean free volume in the material, showed a pattern similar to that obtained for the I3 parameter in the system [TPPO(1-X)×TFNMX]: similar values for the isolated precursors and a linear decreasing until the[TPPO0,5×TFNM0,5] complex formation. The analysis of free-volume values obtained for TPPO, TFNM and complex [TPPO0,5×TFNM0,5] suggests a correlation with the normalized unit cell volume. During themeasurement of the positron lifetime in the system [TPPO(1-X)×TFNMX] at low temperature (80 K), no significant changes were observed in the annihilation parameters throughout exposure time to the source ofpositrons. Notwithstanding, these parameters were sensitive to the effect of low temperature. The whole system presented t3 and I3 values significantly lower than those obtained at 294 K, except for TPPO. Theseresults suggest that at low temperatures the interactions are favored due to the decrease in the rotational and vibrational energies. The preparation and investigation of the system [TPPO(1-X)×ACTLX] was pursuit just as described for [TPPO(1-X)×TFNMX]. The single crystal diffraction results obtained for the complex [TPPO0,5×ACTL0,5] confirms the bonding between TPPO and ACTL (1:1). The melting temperature of the complex[TPPO0,5×ACTL0,5] is smaller than those obtained for the isolated precursors, TPPO and ACTL. These results suggest that the interactions stablished in the supramolecular complex [TPPO0,5×ACTL0,5] are weaker than those existing in the isolated precursors. FTIR-ATR confirmed the formation of hydrogen bonding (C6H5)3P=O-H× × ×NC8H8O through the displacement of P=O band to the lower energy region and N-H and C=O to a higher energy region. The results obtained by EVMP at 294 K for ACTL and TPPO are quite similar when we consider the uncertainties in the measurements. However, in the complex[TPPO0,5×ACTL0,5] these parameters are significantly affected. These results confirm that the phenomenon of positron-matter interaction is very sensitive to complex formation. The relatively higher value obtained forthe probability of positronium formation parameter in the complex [TPPO0,5×ACTL0,5], when compared to their isolated precursors, was associated with relatively weaker interactions formed, according to the results of the previously mentioned techniques. The analysis of free volume values obtained for TPPO, ACTL and complex [TPPO0,5×ACTL0,5] suggest a correlation with the normalized unit cell volume. The positron lifetime measurements at low temperature (80 K) for the [TPPO(1-X)×ACTLX] shows that no significant changes areobserved in annihilation parameters, with the variation of exposure time to the material source of positrons. The annihilation parameters were sensitive to the effect of low temperature. The I3 parameter particularly had its values significantly changed when compared to values obtained at 294 K. In an opposite trend, a linear decrease of I3 was observed as the complex [TPPO0,5×ACTL0,5] is formed. This result corroborates theunderstanding that at low temperatures the interactions are favored by the decrease of the rotational and vibrational energies. Positron lifetime studies on substituted aromatic compounds were also conducted in this work. We used benzene and naphthalene derivatives substituted in the ortho-, meta- and para- by -NH2, -OH, -CN and -NO2 groups. In compounds containing electron donor groups attached to the aromatic ring a high probability of positronium formation was observed and in compounds containing electron withdrawing groups, a lowprobability of positronium formation was observed. The parameters on the probability of positronium formation obtained for the meta- and para- substituted aromatic compounds were correlated with Hammettsigma constants (sm, sp) and compared with Brown-Okamoto constant (p s + ). The correlation curves obtained allowed to re-write the Hammett equation in terms of ratio I3f and I3. All results detailed herein show that EVMP is a very promising technique to study supramolecular complexes, especially in what concerns the electronic effects arising from intermolecular interactions, as well as the crystallographic packing profile that arises. Beside intermolecular effects, the annihilation parameters (mainly o-Ps probability) are also sensitive to the intramolecular effects, as the donating or withdrawing electron density ability through inductive or mesomeric effect